A 3D-printed sulfonated polyether ether ketone composite material in-situ grown with ZIF-62, and a preparation method and application thereof

CN122878627APending Publication Date: 2026-10-09LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611293987.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,3D打印多孔PEEK在干摩擦工况下面临摩擦系数高、耐磨性差的共性技术瓶颈,难以满足苛刻服役条件下对长寿命、高可靠性摩擦部件的迫切需求

Benefits of technology

[0003]有鉴于此,本发明的目的在于提供一种原位生长ZIF-62的3D打印磺化聚醚醚酮复合材料及其制备方法和应用。利用上述制备方法制备得到的原位生长ZIF-62的3D打印磺化聚醚醚酮复合材料具有优异的力学性能和卓越的减摩抗磨性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878627A_ABST
    Figure CN122878627A_ABST
Patent Text Reader

Abstract

The present application relates to polyether ether ketone composite material technical field, especially in situ growth ZIF-62's 3D printing sulfonated polyether ether ketone composite material and its preparation method and application.The preparation method provided by the present application comprises the following steps: 3D printing is used to prepare polyether ether ketone porous material; the polyether ether ketone porous material is sulfonated in concentrated sulfuric acid to obtain sulfonated polyether ether ketone; the sulfonated polyether ether ketone is placed in the precursor solution of ZIF-62, and solvent thermal reaction is carried out to obtain the in-situ growth ZIF-62's 3D printing sulfonated polyether ether ketone composite material; the sulfonation temperature is room temperature, the time is 0-10 min, and it is not 0.The in-situ growth ZIF-62's 3D printing sulfonated polyether ether ketone composite material prepared by the above preparation method has excellent mechanical properties and excellent friction and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyetheretherketone (PEEK) composite materials, and more particularly to a 3D-printed sulfonated PEEK composite material with in-situ ZIF-62 growth, its preparation method, and its application. Background Technology

[0002] Polyetheretherketone (PEEK) has established itself as a core structural material in high-end manufacturing fields such as aerospace, precision medical devices, and humanoid robot joints due to its excellent mechanical strength, thermal stability, chemical corrosion resistance, and biocompatibility. The rapid development of fused deposition modeling (FDM) 3D printing technology has further endowed PEEK with the ability to freely form complex structures, especially its porous structure, which exhibits unique advantages in applications such as bone repair scaffolds and load-bearing lubrication components. However, 3D-printed porous PEEK faces common technical bottlenecks under dry friction conditions, including high friction coefficients and poor wear resistance, making it difficult to meet the urgent needs for long-life, high-reliability friction components under harsh service conditions. To address this, researchers have attempted to improve its tribological properties through surface modification strategies. However, how to effectively enhance its friction-reducing and wear-resistant capabilities through surface functionalization while maintaining the excellent properties of the 3D-printed porous PEEK matrix remains a key technical problem that urgently needs to be solved. Summary of the Invention

[0003] In view of this, the purpose of this invention is to provide a 3D-printed sulfonated polyether ether ketone (PEEK) composite material with in-situ ZIF-62 growth, its preparation method, and its application. The 3D-printed sulfonated PEEK composite material with in-situ ZIF-62 growth prepared using the above method exhibits excellent mechanical properties and superior friction-reducing and wear-resistant properties.

[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing 3D-printed sulfonated polyether ether ketone composite material with in-situ growth of ZIF-62, comprising the following steps: Porous polyetheretherketone (PEEK) materials were prepared using 3D printing. The polyether ether ketone porous material was sulfonated in concentrated sulfuric acid to obtain sulfonated polyether ether ketone. The sulfonated polyether ether ketone was placed in a ZIF-62 precursor solution and subjected to a solvothermal reaction to obtain the 3D printed sulfonated polyether ether ketone composite material of in-situ grown ZIF-62. The sulfonation temperature is room temperature, and the time is 0~10 min, but not 0.

[0005] Preferably, the 3D printing conditions are as follows: nozzle temperature 390~450℃, base plate temperature 25~220℃, cavity temperature 25~220℃, nozzle diameter 0.2~0.4mm, printing speed 20~40mm / s, layer thickness 0.1~0.3mm, infill density 70%~100%, and infill path [45° / -45°] cross-fill.

[0006] Preferably, the concentrated sulfuric acid has a mass percentage concentration of ≥98%.

[0007] Preferably, the precursor solution of ZIF-62 includes imidazole, benzimidazole, zinc nitrate hexahydrate, and an organic solvent.

[0008] Preferably, the molar ratio of zinc nitrate hexahydrate, imidazole, and benzimidazole is 1:(0.25~1.75):(0.25~1.75). The molar ratio of zinc nitrate hexahydrate to the volume ratio of the organic solvent is 1 mol: (60~100) mL.

[0009] Preferably, the temperature of the solvothermal reaction is 100~150℃ and the time is 10~24h.

[0010] The present invention also provides a 3D printed sulfonated polyether ether ketone composite material with in-situ ZIF-62 grown by the preparation method described above, comprising a sulfonated polyether ether ketone matrix and ZIF-62 crystals loaded on the surface and internal pore walls of the sulfonated polyether ether ketone matrix.

[0011] Preferably, the sulfonated polyether ether ketone matrix is ​​a microporous network; The ZIF-62 crystal is a polyhedral crystal.

[0012] This invention also provides the application of the 3D-printed sulfonated polyether ether ketone composite material with in-situ ZIF-62 growth as described above in the field of lubrication.

[0013] This invention provides a method for preparing a 3D-printed sulfonated polyether ether ketone (PEEK) composite material with in-situ ZIF-62 growth, comprising the following steps: preparing a porous PEEK material using 3D printing; sulfonating the porous PEEK material in concentrated sulfuric acid to obtain sulfonated PEEK; placing the sulfonated PEEK in a ZIF-62 precursor solution and performing a solvothermal reaction to obtain the 3D-printed sulfonated PEEK composite material with in-situ ZIF-62 growth; the sulfonation temperature is room temperature, and the time is 0-10 min, not 0. This invention is the first to introduce ZIF-62 in-situ into a 3D-printed sulfonated PEEK composite material system. Using 3D-printed porous PEEK as a matrix, the surface sulfonic acid group density and hierarchical pore structure are precisely controlled by adjusting the sulfonation time, and the 3D-printed sulfonated PEEK composite material with in-situ ZIF-62 growth is successfully prepared using a solvothermal method. The 3D-printed sulfonated polyether ether ketone composite material with in-situ grown ZIF-62 prepared by the above method has excellent mechanical properties and outstanding friction reduction and wear resistance.

[0014] This invention also provides a 3D-printed sulfonated polyetheretherketone (PEEK) composite material with in-situ ZIF-62 growth prepared by the preparation method described above. The composite material comprises a sulfonated PEEK matrix and ZIF-62 crystals loaded on the surface and internal pore walls of the PEEK matrix. In the 3D-printed sulfonated PEEK composite material with in-situ ZIF-62 growth described in this invention, a strong interfacial bond between ZIF-62 and the sulfonated PEEK matrix is ​​achieved through hydrogen bonding and mechanical interlocking effects between the sulfonic acid groups on the PEEK surface and the ZIF-62 ligands. Attached Figure Description

[0015] Figure 1 Schematic diagrams of pin-ring contact mode and ring-block contact mode; Figure 2 The FT-IR spectra of the sulfonated polyether ether ketone (SPEEK), ZIF-62 / SP-2, ZIF-62 / SP-4, ZIF-62 / SP-6 and ZIF-62 / SP-8 composite materials described in Examples 1-4 and the XRD spectrum of ZIF-62 / SP-6 are shown. Figure 3 Microstructure and EDS elemental analysis of 3D-printed sulfonated polyether ether ketone composites with ZIF-62 grown in situ at different sulfonation times; Figure 4 The SEM morphology and EDS elemental distribution of the 3D printed holes, wear surface, and transfer film of the 3D printed ZIF-62 in-situ grown sulfonated polyether ether ketone composite material described in Example 3 in the pin-ring contact mode are shown. Figure 5The SEM morphology and EDS elemental distribution of the 3D printed holes, wear surface, and transfer film of the 3D printed ZIF-62 in-situ grown sulfonated polyether ether ketone composite material described in Example 3 are shown in the ring-block contact mode. Detailed Implementation

[0016] This invention provides a method for preparing 3D-printed sulfonated polyether ether ketone composite material with in-situ growth of ZIF-62, comprising the following steps: Porous polyetheretherketone (PEEK) materials were prepared using 3D printing. The polyether ether ketone porous material was sulfonated in concentrated sulfuric acid to obtain sulfonated polyether ether ketone. The sulfonated polyether ether ketone was placed in a ZIF-62 precursor solution and subjected to a solvothermal reaction to obtain the 3D printed sulfonated polyether ether ketone composite material of in-situ grown ZIF-62. The sulfonation temperature is room temperature, and the time is 0~10 min, but not 0.

[0017] In this invention, unless otherwise specified, all raw materials used in the preparation are commercially available products well known to those skilled in the art.

[0018] This invention uses 3D printing to prepare polyetheretherketone porous materials.

[0019] In this invention, the raw material for 3D printing is preferably PEEK filament.

[0020] In this invention, the preferred conditions for 3D printing are: nozzle temperature preferably 390~450℃, more preferably 390℃, 400℃, 410℃, 420℃, 430℃, 440℃, or 450℃; base plate temperature preferably 25~220℃, more preferably 25℃, 40℃, 60℃, 80℃, 100℃, 120℃, 140℃, 160℃, 180℃, 200℃, or 220℃; cavity temperature preferably 25~220℃, more preferably 25℃, 40℃, 60℃, 80℃, 100℃, 120℃, 140℃, 160℃, 180℃, or 220℃; The printing temperature is ℃, 200℃, or 220℃; the nozzle diameter is preferably 0.2~0.4mm, more preferably 0.2mm, 0.3mm, or 0.4mm; the printing speed is preferably 20~40mm / s, more preferably 20mm / s, 25mm / s, 30mm / s, 35mm / s, or 40mm / s; the layer thickness is preferably 0.1~0.3mm, more preferably 0.1mm, 0.2mm, or 0.3mm; the filling density is preferably 70%~100%, more preferably 70%, 80%, 90%, or 100%; the filling path is preferably [45° / -45°] cross-filling.

[0021] After the 3D printing is completed, the present invention preferably includes sequential cleaning and drying. The cleaning is preferably performed using isopropanol for ultrasonic cleaning. The drying temperature is preferably 70~100℃, more preferably 70℃, 80℃, 90℃ or 100℃. The drying time is preferably 4~12h, more preferably 4h, 6h, 8h, 10h or 12h.

[0022] In this invention, the polyetheretherketone porous material has regular macroscopic pores with a pore size of 200~250μm×200~250μm.

[0023] After obtaining the polyether ether ketone porous material, the present invention sulfonates the polyether ether ketone porous material in concentrated sulfuric acid to obtain sulfonated polyether ether ketone.

[0024] In this invention, the mass percentage concentration of the concentrated sulfuric acid is preferably ≥98%.

[0025] In this invention, the sulfonation temperature is preferably room temperature, and the time is preferably 0 to 10 min, but not 0, and more preferably 2 min, 4 min, 6 min, 8 min or 10 min.

[0026] In this invention, after sulfonation, a microporous network is preferably formed on the inner wall of the macropores and the surface of the polyether ether ketone porous material.

[0027] In this invention, the sulfonated polyether ether ketone surface contains sulfonic acid groups (-SO3H), and the density of the sulfonic acid groups on the polyether ether ketone surface can be precisely adjusted by controlling the sulfonation time.

[0028] After the sulfonation is completed, the present invention preferably includes a termination reaction, washing, and drying performed sequentially; the termination reaction is preferably performed by rapidly immersing the product obtained after sulfonation in deionized water to terminate the reaction; the washing process is not particularly limited in the present invention, and can be carried out using a process well known to those skilled in the art, and the washed product should be neutral; the drying temperature is preferably 100°C. After obtaining the sulfonated polyether ether ketone, the present invention places the sulfonated polyether ether ketone in a precursor solution of ZIF-62 and performs a solvothermal reaction to obtain the 3D printed sulfonated polyether ether ketone composite material of in-situ grown ZIF-62.

[0029] In this invention, the precursor solution of ZIF-62 preferably includes imidazole, benzimidazole, zinc nitrate hexahydrate, and an organic solvent.

[0030] In this invention, the organic solvent preferably includes N,N-dimethylformamide and / or methanol; when the organic solvent is N,N-dimethylformamide and methanol, this invention does not impose any special limitation on the ratio of N,N-dimethylformamide and methanol, and they can be mixed in any ratio.

[0031] In this invention, the molar ratio of zinc nitrate hexahydrate, imidazole, and benzimidazole is preferably 1:(0.25~1.75):(0.25~1.75), more preferably 1:0.25:(0.25~1.75), 1:0.5:(0.25~1.75), 1:0.75:(0.25~1.75), 1:1:(0.25~1.75), 1:1.25:(0.25~1.75), or 1:1.5:( 0.25~1.75), 1:1.75:(0.25~1.75), 1:(0.25~1.75):0.25, 1:(0.25~1.75):0.5, 1:(0.25~1.75):0.75, 1:(0.25~1.75):1, 1:(0.25~1.75):1.25, 1:(0.25~1.75):1.5 or 1:(0.25~1.75):1.75.

[0032] In this invention, the molar ratio of zinc nitrate hexahydrate to the volume ratio of the organic solvent is preferably 1 mol: (60~100) mL, more preferably 1 mol: 60 mL, 1 mol: 70 mL, 1 mol: 80 mL, 1 mol: 90 mL or 1 mol: 100 mL.

[0033] In this invention, the preparation method of the ZIF-62 precursor solution preferably includes mixing imidazole, benzimidazole, zinc nitrate hexahydrate, and an organic solvent to obtain the ZIF-62 precursor solution. In this invention, the mixing is preferably carried out under magnetic stirring conditions, and the magnetic stirring time is preferably 10-30 min, more preferably 10 min, 15 min, 20 min, 25 min, or 30 min.

[0034] In this invention, the preferred volume ratio of the number of sulfonated polyether ether ketones to the ZIF-62 precursor solution is (2~6) units: (60~100) mL, 2 units: (60~100) mL, more preferably 4 units: (60~100) mL, 6 units: (60~100) mL, (2~6) units: 60 mL, (2~6) units: 70 mL, (2~6) units: 80 mL, (2~6) units: 90 mL, or (2~6) units: 100 mL. In this invention, the preferred size of each tribological test sulfonated polyether ether ketone is 4 mm × 4 mm × 12 mm. The preferred size of each tensile test sulfonated polyether ether ketone is 90 mm × 10 mm × 2 mm.

[0035] In this invention, the temperature of the solvothermal reaction is preferably 100~150℃, more preferably 100℃, 110℃, 120℃, 130℃, 140℃ or 150℃; the time is preferably 10~24h, more preferably 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.

[0036] After the solvothermal reaction is completed, the present invention preferably includes sequential rinsing and drying; the rinsing is preferably performed by repeated rinsing with DMF solvent to remove unreacted substances physically adsorbed on the surface; the drying temperature is preferably 100°C.

[0037] The present invention also provides a 3D printed sulfonated polyether ether ketone composite material with in-situ ZIF-62 grown by the preparation method described above, comprising a sulfonated polyether ether ketone matrix and ZIF-62 crystals loaded on the surface and internal pore walls of the sulfonated polyether ether ketone matrix.

[0038] In this invention, the sulfonated polyether ether ketone matrix is ​​preferably a microporous network; The ZIF-62 crystal is preferably a polyhedral crystal.

[0039] This invention also provides the application of the 3D-printed sulfonated polyether ether ketone composite material with in-situ ZIF-62 growth described above in the field of lubrication. This invention does not impose any special limitations on the method of application; any method well-known to those skilled in the art can be used.

[0040] The following detailed description, in conjunction with embodiments, illustrates the in-situ grown ZIF-62 3D-printed sulfonated polyether ether ketone composite material, its preparation method, and its applications provided by the present invention. However, these descriptions should not be construed as limiting the scope of protection of the present invention.

[0041] Example 1 1) 3D printing: FDM 3D printer (Doctor 300) was used for printing: nozzle temperature: 440℃, base plate temperature: 220℃, cavity temperature: 200℃, nozzle diameter: 0.4mm, printing speed: 30mm / s, layer height: 0.2mm, 90% infill density, [45° / -45°] cross infill path, to print PEEK pin samples (4mm×4mm×12mm) and PEEK dumbbell tensile specimens (90mm×10mm×2mm); the obtained PEEK pin samples and PEEK dumbbell tensile specimens were ultrasonically cleaned with isopropanol and dried at 80℃ for 5h to obtain dried PEEK samples; 2) Sulfonation: The dried PEEK sample was immersed in concentrated sulfuric acid (concentration ≥98wt%) and reacted at room temperature for 2 min. Then, it was quickly immersed in deionized water to terminate the reaction. The sample was repeatedly washed with deionized water until pH=7 and dried at 100℃ for 10 h to obtain sulfonated polyether ether ketone sample (SP-2 sample). 3) Preparation of precursor solution: 8.91g imidazole, 1.55g benzimidazole and 1.65g zinc nitrate hexahydrate were added sequentially to 80mL of DMF solvent and stirred magnetically for 30min until completely dissolved to obtain the precursor solution; 4) In-situ growth: Four SP-2 samples were immersed in the precursor solution, transferred to a polytetrafluoroethylene-lined reactor, sealed, and reacted at a constant temperature of 130°C for 12 hours. After rinsing with DMF, the samples were dried in an oven at 100°C to obtain the ZIF-62 / SP-2 composite material. Mechanical property testing: The ZIF-62 / SP-2 composite material was subjected to tensile testing according to GB / T 1040.1-2006. The test conditions were: tensile test speed of 1 mm / min; the test results were: the tensile strength of the PEEK composite material sample was 33.80 MPa and the tensile modulus was 1815.7 MPa. Tribological performance testing (pin-ring contact mode, test diagram as shown) Figure 1 As shown in (a)): Load: 4MPa, sliding speed: 1m / s, test time: 2h; all dried PEEK samples were pre-ground before testing to ensure that the sample and the surface of the mating steel ring (GCr15, radius 50mm) were fully in contact, and then the above sulfonation treatment was performed to test the tribological properties of the sulfonated polyether ether ketone sample. The coefficient of friction (COF) is the average value after friction enters the stable stage, and the average coefficient of friction is the average of the coefficients of friction from three parallel experiments. The mass wear rate (Ws) is calculated using Equation 1: where, Δm The mass loss (g) of the sample before and after the test. L The total sliding distance (m) is calculated from the sliding speed and the test time.F The normal load is (N). ρ Sample density (g / cm³) 3 ).

[0042] Formula 1; Test results: The average mass wear rate of the sulfonated polyether ether ketone composite material sample was 8.20 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.36; Tribological performance testing (ring-block contact mode, test diagram as shown) Figure 1 (as shown in (b)): Contact stress: 60 N, sliding speed: 1 m / s, test time: 2 h; The coefficient of friction (COF) is the average value after friction enters the stable stage, and the average coefficient of friction is the average of the coefficients of friction from three parallel experiments. The volumetric wear rate (Ws) is calculated according to Equation 2: where, B The width of the pin sample (mm). W Width of the wear mark (mm). R The radius of the mating component is (mm). F The normal load is (N). L The total sliding distance is (m).

[0043] Formula 2; Test results: The average mass wear rate of the sulfonated polyether ether ketone composite material sample was 2.85 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.34.

[0044] Example 2 1) 3D printing: FDM 3D printer (Doctor 300) was used for printing: nozzle temperature: 440℃, base plate temperature: 220℃, cavity temperature: 200℃, nozzle diameter: 0.4mm, printing speed: 30mm / s, layer height: 0.2mm, 90% infill density, [45° / -45°] cross infill path, to print PEEK pin samples (4mm×4mm×12mm) and PEEK dumbbell tensile specimens (90mm×10mm×2mm); the obtained PEEK pin samples and PEEK dumbbell tensile specimens were ultrasonically cleaned with isopropanol and dried at 80℃ for 5h to obtain dried PEEK samples; 2) Sulfonation: The dried PEEK sample was immersed in concentrated sulfuric acid (concentration ≥98wt%) and reacted at room temperature for 4 min. Then, it was quickly immersed in deionized water to terminate the reaction. The sample was repeatedly washed with deionized water until pH=7 and dried at 100℃ for 10 h to obtain sulfonated polyether ether ketone sample (SP-4 sample). 3) Preparation of precursor solution: 8.91g imidazole, 1.55g benzimidazole and 1.65g zinc nitrate hexahydrate were added sequentially to 80mL of DMF solvent and stirred magnetically for 30min until completely dissolved to obtain the precursor solution; 4) In-situ growth: Four SP-4 samples were immersed in the precursor solution, transferred to a polytetrafluoroethylene-lined reactor, sealed, and reacted at a constant temperature of 130°C for 12 hours. After rinsing with DMF, the samples were dried in an oven at 100°C to obtain the ZIF-62 / SP-4 composite material. Mechanical property testing: Referring to Example 1, the test results are as follows: the tensile strength of the ZIF-62 / SP-4 composite material is 34.70 MPa, and the tensile modulus is 2093.8 MPa; Tribological performance testing (pin-ring contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the sulfonated polyether ether ketone composite sample was 6.35 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.34; Tribological performance testing (ring-block contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the sulfonated polyether ether ketone composite sample was 2.53 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.33.

[0045] Example 3 1) 3D printing: FDM 3D printer (Doctor 300) was used for printing: nozzle temperature: 440℃, base plate temperature: 220℃, cavity temperature: 200℃, nozzle diameter: 0.4mm, printing speed: 30mm / s, layer height: 0.2mm, 90% infill density, [45° / -45°] cross infill path, to print PEEK pin samples (4mm×4mm×12mm) and PEEK dumbbell tensile specimens (90mm×10mm×2mm); the obtained PEEK pin samples and PEEK dumbbell tensile specimens were ultrasonically cleaned with isopropanol and dried at 80℃ for 5h to obtain dried PEEK samples; 2) Sulfonation: The dried PEEK sample was immersed in concentrated sulfuric acid (concentration ≥98wt%) and reacted at room temperature for 6 min. Then, it was quickly immersed in deionized water to terminate the reaction. The sample was repeatedly washed with deionized water until pH=7 and dried at 100℃ for 10 h to obtain sulfonated polyether ether ketone sample (SP-6 sample). 3) Preparation of precursor solution: 8.91g imidazole, 1.55g benzimidazole and 1.65g zinc nitrate hexahydrate were added sequentially to 80mL of DMF solvent and stirred magnetically for 30min until completely dissolved to obtain the precursor solution; 4) In-situ growth: Four SP-6 samples were immersed in the precursor solution, transferred to a polytetrafluoroethylene-lined reactor, sealed, and reacted at a constant temperature of 130°C for 12 hours. After rinsing with DMF, the samples were dried in an oven at 100°C to obtain the ZIF-62 / SP-6 composite material. Mechanical property testing: Referring to Example 1, the test results are as follows: the tensile strength of the ZIF-62 / SP-6 composite material is 35.45 MPa, and the tensile modulus is 2123.1 MPa; Tribological performance testing (pin-ring contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the sulfonated polyether ether ketone composite sample was 4.99 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.33; Tribological performance testing (ring-block contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the sulfonated polyether ether ketone composite sample was 2.21 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.31.

[0046] Example 4 1) 3D printing: FDM 3D printer (Doctor 300) was used for printing: nozzle temperature: 440℃, base plate temperature: 220℃, cavity temperature: 200℃, nozzle diameter: 0.4mm, printing speed: 30mm / s, layer height: 0.2mm, 90% infill density, [45° / -45°] cross infill path, to print PEEK pin samples (4mm×4mm×12mm) and PEEK dumbbell tensile specimens (90mm×10mm×2mm); the obtained PEEK pin samples and PEEK dumbbell tensile specimens were ultrasonically cleaned with isopropanol and dried at 80℃ for 5h to obtain dried PEEK samples; 2) Sulfonation: The dried PEEK sample was immersed in concentrated sulfuric acid (concentration ≥98wt%) and reacted at room temperature for 8 min. Then, it was quickly immersed in deionized water to terminate the reaction. The sample was repeatedly washed with deionized water until pH=7 and dried at 100℃ for 10 h to obtain sulfonated polyether ether ketone sample (SP-8 sample). 3) Preparation of precursor solution: 8.91g imidazole, 1.55g benzimidazole and 1.65g zinc nitrate hexahydrate were added sequentially to 80mL of DMF solvent and stirred magnetically for 30min until completely dissolved to obtain the precursor solution; 4) In-situ growth: Four SP-8 samples were immersed in the precursor solution, transferred to a polytetrafluoroethylene-lined reactor, sealed, and reacted at a constant temperature of 130°C for 12 hours. After rinsing with DMF, the samples were dried in an oven at 100°C to obtain the ZIF-62 / SP-8 composite material. Mechanical property testing: Referring to Example 1, the test results are as follows: the tensile strength of the ZIF-62 / SP-8 composite material is 33.68 MPa, and the tensile modulus is 2046.0 MPa; Tribological performance testing (pin-ring contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the sulfonated polyether ether ketone composite sample was 1.28 × 10⁻⁶. -5 mm 3 / N·m, with an average friction coefficient of 0.37; Tribological performance testing (ring-block contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the sulfonated polyether ether ketone composite sample was 4.30 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.37.

[0047] Example 5 1) 3D printing: An FDM 3D printer (Doctor 300) was used for printing: Nozzle temperature: 440℃, base plate temperature: 220℃, cavity temperature: 200℃, nozzle diameter: 0.4mm, printing speed: 30mm / s, layer height: 0.2mm, 90% infill density, [45° / -45°] cross-infill path, to print PEEK pin samples (4mm×4mm×12mm); the obtained PEEK pin samples were ultrasonically cleaned with isopropanol and dried at 80℃ for 5 hours to obtain dried PEEK samples; 2) Sulfonation: The dried PEEK sample was immersed in concentrated sulfuric acid (concentration ≥98wt%) and reacted at room temperature for 8 min. Then, it was quickly immersed in deionized water to terminate the reaction. The sample was repeatedly washed with deionized water until pH=7 and dried at 100℃ for 10 h to obtain sulfonated polyether ether ketone sample (SP-8 sample). 3) Preparation of precursor solution: 8.91g imidazole, 1.55g benzimidazole and 1.65g zinc nitrate hexahydrate were added sequentially to 80mL of DMF solvent and stirred magnetically for 30min until completely dissolved to obtain the precursor solution; 4) In-situ growth: Four SP-8 samples were immersed in the precursor solution, transferred to a polytetrafluoroethylene-lined reactor, sealed, and reacted at a constant temperature of 130°C for 24 hours. After rinsing with DMF, the samples were dried in an oven at 100°C to obtain the ZIF-62 / SP-8 composite material. Tribological performance testing (pin-ring contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the sulfonated polyether ether ketone composite sample was 7.93 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.41.

[0048] Example 6 1) 3D printing: An FDM 3D printer (Doctor 300) was used for printing: Nozzle temperature: 440℃, base plate temperature: 220℃, cavity temperature: 200℃, nozzle diameter: 0.4mm, printing speed: 30mm / s, layer height: 0.2mm, 90% infill density, [45° / -45°] cross-infill path, to print PEEK pin samples (4mm×4mm×12mm); the obtained PEEK pin samples were ultrasonically cleaned with isopropanol and dried at 80℃ for 5 hours to obtain dried PEEK samples; 2) Sulfonation: The dried PEEK sample was immersed in concentrated sulfuric acid (concentration ≥98wt%) and reacted at room temperature for 4 min. Then, it was quickly immersed in deionized water to terminate the reaction. The sample was repeatedly washed with deionized water until pH=7 and dried at 100℃ for 10 h to obtain sulfonated polyether ether ketone sample (SP-4 sample). 3) Preparation of precursor solution: 8.91g imidazole, 1.55g benzimidazole and 1.65g zinc nitrate hexahydrate were added sequentially to 80mL of DMF solvent and stirred magnetically for 30min until completely dissolved to obtain the precursor solution; 4) In-situ growth: Four SP-4 samples were immersed in the precursor solution, transferred to a polytetrafluoroethylene-lined reactor, sealed, and reacted at a constant temperature of 130°C for 15 hours. After rinsing with DMF, the samples were dried in an oven at 100°C to obtain the ZIF-62 / SP-4 composite material. Tribological performance testing (pin-ring contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the sulfonated polyether ether ketone composite sample was 8.92 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.38.

[0049] Example 7 1) 3D printing: An FDM 3D printer (Doctor 300) was used for printing: Nozzle temperature: 440℃, base plate temperature: 220℃, cavity temperature: 200℃, nozzle diameter: 0.4mm, printing speed: 30mm / s, layer height: 0.2mm, 90% infill density, [45° / -45°] cross-infill path, to print PEEK pin samples (4mm×4mm×12mm); the obtained PEEK pin samples were ultrasonically cleaned with isopropanol and dried at 80℃ for 5 hours to obtain dried PEEK samples; 2) Sulfonation: The dried PEEK sample was immersed in concentrated sulfuric acid (concentration ≥98wt%) and reacted at room temperature for 6 min. Then, it was quickly immersed in deionized water to terminate the reaction. The sample was repeatedly washed with deionized water until pH=7 and dried at 100℃ for 10 h to obtain sulfonated polyether ether ketone sample (SP-6 sample). 3) Preparation of precursor solution: 8.91g imidazole, 1.55g benzimidazole and 1.65g zinc nitrate hexahydrate were added sequentially to 80mL of DMF solvent and stirred magnetically for 30min until completely dissolved to obtain the precursor solution; 4) In-situ growth: Four SP-6 samples were immersed in the precursor solution, transferred to a polytetrafluoroethylene-lined reactor, sealed, and reacted at a constant temperature of 130°C for 15 hours. After rinsing with DMF, the samples were dried in an oven at 100°C to obtain the ZIF-62 / SP-6 composite material. Tribological performance testing (pin-ring contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the sulfonated polyether ether ketone composite sample was 1.24 × 10⁻⁶. -5 mm 3 / N·m, with an average friction coefficient of 0.38.

[0050] Example 8 1) 3D printing: An FDM 3D printer (Doctor 300) was used for printing: Nozzle temperature: 440℃, base plate temperature: 120℃, cavity temperature: 90℃, nozzle diameter: 0.4mm, printing speed: 30mm / s, layer height: 0.2mm, 90% infill density, [45° / -45°] cross-infill path, to print PEEK pin samples (4mm×4mm×12mm); the obtained PEEK pin samples were ultrasonically cleaned with isopropanol and dried at 80℃ for 5 hours to obtain dried PEEK samples; 2) Sulfonation: The dried PEEK sample was immersed in concentrated sulfuric acid (concentration ≥98wt%) and reacted at room temperature for 6 min. Then, it was quickly immersed in deionized water to terminate the reaction. The sample was repeatedly washed with deionized water until pH=7 and dried at 100℃ for 10 h to obtain sulfonated polyether ether ketone sample (SP-6 sample). 3) Preparation of precursor solution: 8.91g imidazole, 1.55g benzimidazole and 1.65g zinc nitrate hexahydrate were added sequentially to 80mL of DMF solvent and stirred magnetically for 30min until completely dissolved to obtain the precursor solution; 4) In-situ growth: Four SP-6 samples were immersed in the precursor solution, transferred to a polytetrafluoroethylene-lined reactor, sealed, and reacted at a constant temperature of 130°C for 12 hours. After rinsing with DMF, the samples were dried in an oven at 100°C to obtain the ZIF-62 / SP-6 composite material. Tribological performance testing (pin-ring contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the sulfonated polyether ether ketone composite sample was 8.54 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.40.

[0051] Comparative Example 1 Referring to Example 3, SP-6 sample was obtained; Mechanical property testing: Referring to Example 1, the test results are as follows: the tensile strength of the sulfonated PEEK sample is 34.38 MPa, and the tensile modulus is 1848.9 MPa; Tribological performance testing (pin-ring contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the SP-6 sample was 7.97 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.37; Tribological performance testing (ring-block contact mode): Referring to Example 1, the test results showed that the average mass wear rate of the SP-6 sample was 7.52 × 10⁻⁶. -6 mm 3 / N·m, with an average friction coefficient of 0.38.

[0052] In summary, after introducing ZIF-62, the tensile strength and elastic modulus of the composite material first increase and then decrease with the extension of sulfonation time. The tensile strength and tensile modulus of the ZIF-62 / SP-6 composite material reach their maximum values ​​(35.45 MPa and 2123.5 MPa), which are 3.11% and 14.85% higher than those of SP-6, respectively. At this point, a large number of hydrogen bonds are formed between ZIF-62 and SPEEK, enhancing mechanical interlocking and resulting in the strongest interfacial bonding, thus achieving effective stress transfer from the matrix to ZIF-62. According to tribological properties, all printed holes in the ZIF-62 / SP composite material exhibit a raised feature after wear. This indicates that ZIF-62 and the SPEEK matrix enhance intermolecular forces and strengthen interfacial mechanical interlocking through hydrogen bonds. During friction, the wear debris generated by ZIF-62 and the matrix is ​​pressed into the printed holes, improving shear resistance and surface integrity, allowing the wear debris to play a load-bearing and lubricating role, thereby improving the friction-reducing and wear-resistant properties of the composite material.

[0053] Test case Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) tests: Figure 2 The images show the FT-IR spectra of the sulfonated polyether ether ketone (SPEEK), ZIF-62 / SP-2, ZIF-62 / SP-4, ZIF-62 / SP-6, and ZIF-62 / SP-8 composite materials described in Examples 1-4, and the XRD pattern of ZIF-62 / SP-6. (a) is the FT-IR spectrum of the sulfonated polyether ether ketone; (b) is the FT-IR spectrum of the ZIF-62 / SP-2, ZIF-62 / SP-4, ZIF-62 / SP-6, and ZIF-62 / SP-8 composite materials; and (c) is the XRD pattern of the ZIF-62 / SP-6 composite material. Figure 2 It can be seen that the SPEEK sample retains the characteristic peaks of the PEEK backbone while exhibiting peaks at 1250 cm⁻¹. -1 and 1050 cm -1 The presence of characteristic absorption peaks of sulfonic acid groups (-SO3H) nearby confirms that sulfonic acid groups have been successfully introduced into the PEEK molecular chain; the ZIF-62 / SP composite material retains all characteristic peaks of SPEEK and adds characteristic absorption peaks of ZIF-62 (754, 952, 1063, 660 cm⁻¹). -1 The presence of characteristic XRD diffraction peaks confirmed that ZIF-62, with a complete crystal structure, has been successfully synthesized in situ on a SPEEK matrix.

[0054] Figure 3For the microstructure and EDS elemental analysis of 3D-printed sulfonated polyether ether ketone (PEEK) composites with in-situ ZIF-62 growth at different sulfonation times, a1~a7 represent the microstructure and EDS elemental analysis of the 3D-printed sulfonated PEEK composites with in-situ ZIF-62 growth described in Example 1; b1~b7 represent the microstructure and EDS elemental analysis of the 3D-printed sulfonated PEEK composites with in-situ ZIF-62 growth described in Example 2; c1~c7 represent the microstructure and EDS elemental analysis of the 3D-printed sulfonated PEEK composites with in-situ ZIF-62 growth described in Example 3; d1~d7 represent the microstructure and EDS elemental analysis of the 3D-printed sulfonated PEEK composites with in-situ ZIF-62 growth described in Example 4. Figure 3 It can be seen that, by utilizing the sulfonic acid groups on the SPEEK surface as interfacial coordination anchors, in-situ growth of ZIF-62 crystals was successfully achieved via a solvothermal method, forming a metal-organic framework protective layer on the SPEEK substrate surface and the inner wall of the 3D-printed macroscopic channels. ZIF-62 polyhedral crystals (average particle size approximately 4 μm) were loaded onto the substrate surface and the inner wall of the channels. As the sulfonation time increased from 2 min to 8 min, the coverage density and loading of ZIF-62 crystals significantly improved, indicating that a higher degree of sulfonation can provide more abundant hydrogen bond active sites for the heterogeneous nucleation of ZIF-62. Figure 4 The SEM morphology and EDS elemental distribution of the 3D-printed sulfonated polyetheretherketone composite material with in-situ ZIF-62 growth as described in Example 3, in pin-ring contact mode, are obtained from... Figure 4 It can be seen that the 3D printed pores of the in-situ grown ZIF-62 sulfonated polyether ether ketone composite material are fully filled and compacted by the grinding debris. Figure 4 (a1 in the text) The worn surface has no obvious ploughing marks. Figure 4 (a2 in the text) A dense, uniform, and continuously covering transfer film was formed on the surface of the paired steel ring. Figure 4 (a3 in the text). EDS energy dispersive spectroscopy analysis showed that characteristic signals of Zn and N elements were detected in the transfer film, and the elements were uniformly distributed, confirming that ZIF-62 participated in the formation of the transfer film and effectively improved its continuity and structural compactness, thereby bearing the load transfer and shearing action and reducing the direct contact of the friction pair; Figure 5 The SEM morphology and EDS elemental distribution of the 3D-printed sulfonated polyetheretherketone composite material with in-situ ZIF-62 growth as described in Example 3, in the ring-block contact mode, are obtained from... Figure 5 It can be seen that the 3D printed pores of the composite material are completely compacted and filled with abrasive debris, and the pore boundaries tend to be blurred. Figure 5 (a1 in the text) The worn surface is flat and smooth. Figure 5(a2 in the text) A continuous and dense transfer film was formed on the surface of the dual steel ring ( Figure 5 (a3 in the text). EDS energy dispersive spectroscopy analysis further confirmed that Zn and N elements were uniformly distributed in the transfer film, indicating that ZIF-62 is stably present at the friction interface and participates in the formation and spreading of the transfer film.

[0055] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing 3D-printed sulfonated polyetheretherketone composite material with in-situ growth of ZIF-62, characterized in that, Includes the following steps: Porous polyetheretherketone (PEEK) materials were prepared using 3D printing. The polyether ether ketone porous material was sulfonated in concentrated sulfuric acid to obtain sulfonated polyether ether ketone. The sulfonated polyether ether ketone was placed in a ZIF-62 precursor solution and subjected to a solvothermal reaction to obtain the 3D printed sulfonated polyether ether ketone composite material of in-situ grown ZIF-62. The sulfonation temperature is room temperature, and the time is 0~10 min, but not 0.

2. The preparation method according to claim 1, characterized in that, The 3D printing conditions are as follows: nozzle temperature 390~450℃, base plate temperature 25~220℃, cavity temperature 25~220℃, nozzle diameter 0.2~0.4mm, printing speed 20~40mm / s, layer thickness 0.1~0.3mm, infill density 70%~100%, and infill path [45° / -45°] cross-fill.

3. The preparation method according to claim 1, characterized in that, The concentrated sulfuric acid has a mass percentage concentration of ≥98%.

4. The preparation method according to claim 1, characterized in that, The precursor solution of ZIF-62 includes imidazole, benzimidazole, zinc nitrate hexahydrate, and an organic solvent.

5. The preparation method according to claim 4, characterized in that, The molar ratio of zinc nitrate hexahydrate, imidazole, and benzimidazole is 1:(0.25~1.75):(0.25~1.75). The molar ratio of zinc nitrate hexahydrate to the volume ratio of the organic solvent is 1 mol: (60~100) mL.

6. The preparation method according to claim 1, characterized in that, The solvothermal reaction is carried out at a temperature of 100-150°C for 10-24 hours.

7. The 3D-printed sulfonated polyether ether ketone composite material with in-situ grown ZIF-62 prepared by the preparation method according to any one of claims 1 to 6, characterized in that, It includes a sulfonated polyether ether ketone matrix and ZIF-62 crystals loaded on the surface and internal pore walls of the sulfonated polyether ether ketone matrix.

8. The 3D-printed sulfonated polyetheretherketone composite material with in-situ ZIF-62 growth as described in claim 7, characterized in that, The sulfonated polyether ether ketone matrix is ​​a microporous network; The ZIF-62 crystal is a polyhedral crystal.

9. The application of the 3D-printed sulfonated polyether ether ketone composite material of in-situ grown ZIF-62 as described in claim 7 or 8 in the field of lubrication.